Fertility Histories and Heart Disease in Later Life in China - Wu, Yuanyang; Pang, Jiahui; Wang, Jiahao; Wu, Jing; Zhang, Shuo; Zhang, Siqing; Yao, Yidan; Cheng, Simeng; Tao, Yiwen; Shen, Zheng; Li, Zhi-yun; Xie, Lin; et al. (Frontiers in Public Health, 2022)
Purpose: Based on life course theories, health among older people is driven by a continuous and cumulative process that develops over the life course. To better understand the ageing process, it is important to assess associations between parity and heart disease in Chinese older people. Method: The associations between heart disease prevalence and number of births, number of boys or girls ever born were evaluated among 4284 samples (mean age 68.4 years) using Probit regression model based on the data from China Health and Retirement Longitudinal Study (CHARLS) conducted in 2013.Then,we adjusted the model only for rural or urban residents, and we ran multivariate regression models separately by gender. Results: Our results showed that high parity and more boys ever born were associated with higher risk of heart disease. However, number of girls ever born had no significant effect on heart disease of the elderly. We further analyzed the group difference of urban-rural using the regression. High parity and more boys ever born were associated high risk of heart disease in rural areas. Compared to urban residents, rural residents were more likely to be suffering from heart disease duo to high parity. Models adjusted for different gender indicated that more boys ever born were associated with high risk of heart disease both in male and female. Late age at entry to parenthood was associated with poorer risk level of heart disease, but after adjusting for different gender, the association disappeared in men. This association remained significant after adjusting for rural residents only. Conclusions: First, parents who were ready to give birth should be aware of the possible health loss of high parity. Postpartum nutrition supplement and chronic disease prevention were suggested to prevent heart disease in later life. Secondly, the elderly in rural areas should pay more attention to the heart disease. Participating in more daily exercise and physical examinations were a good choice to reduce the risk of heart disease. Thirdly, early age at entry to parenthood was not advocated.